Adaptive Neuro-Fuzzy Optimization of the Net Present Value and Internal Rate of Return of a Wind Farm Project under Wake Effect - Petković, Dalibor (2015)
According to studies on the impossible trinity, under conditions of high financial integration, the domestic interest rate is closely linked to the foreign one if the possibility of maneuvering interest rates is absent in this transaction. The Fisher effect is brought into this escapade because interest rates generally trend positively with inflation. Botswana has set her inflation target between 3-6% and this study attempts to determine inflation spillover effects from the United Kingdom, United States of America, Canada, Japan, China, Belgium, France, Germany, South Africa, Nigeria, and Ghana using data from 1980-2012. Comparatively, the attempts made by previous studies to examine spillovers generally lacked a long-run focus and channeled much attention to periods of financial crisis. This study deviates from other studies by using the Augmented Dickey Fuller (ADF) test to examine unit roots for the countries under examination. The study further applies the Johansen cointegration procedure, as well as the Granger causality test. The results show that Botswana’s inflation dynamics trend positively with all the countries under scrutiny except South Africa in a long-run framework. However, the Granger causality test only proved that Botswana’s inflation lead China’s inflation dynamics. In conclusion, Botswana’s inflation is not driven by other countries’ inflation dynamics.